Candidate Programs as a Genre of Political Rhetoric - Biržietienė, Skirmantė; Gabrėnaitė, Eglė (Respectus Philologicus, 2021)
Candidate programs are a publication of political parties during the agitation campaign, which presents the political attitudes of a political actor and influence voters’ motivation to vote in elections. The electoral candidate program illustrates a politician’s relationship with voters. It is an element of political communication, part of the image of a political figure. The article deals with the rhetoric of electoral candidate programs announced before the elections to the Seimas, the European Parliament, and Municipal Councils (2014–2019). The aim is to identify and expand the characteristic rhetorical elements that allow qualifying political electoral programs as a specific genre of political rhetoric: at the inventive level, the study of rhetorical strategies includes the analysis of rhetorical reasoning, the relationship between a political actor and a voter; at the dispositional level, the composition of programs is analyzed; and finally, at the elocutionary level, the specifics of the linguistic expression of discourse are investigated. A rhetorical study of discourse revealed that, in many cases, the electoral candidate program functions as a tool for building the image of a political actor, a tool for discrediting opponents and spreading populist promises.
Keywords: political rhetoric; candidate program; invention; disposition; elocution